Analytical method validation for determination of total mercury in human blood by zeeman mercury spectrometer ra-915+ with the pyrolysis module pyro-915+ (2013)
This article describes the methodology of the validation about the identification of total mercury in blood samples by Zeeman atomic absorption spectrophotometry RA-915+ with the module of Pyrolysis PYRO-915+, suitable for the direct determination of total mercury concentrations in various matrices, that unlike other atomization techniques (graphite furnace, cold vapor or hydride generator) does not require a sample pre-treatment. With the application of this validation, is provided the reliability in the results. Most of the validation parameters were subjected to analysis of variance ANOVA with a confidence level of 95%. It was obtained a detection limit of 2.16 µg/L, a quantitation limit of 5.54µg/L and linearity in the range of 5.54 µg/L to , in addition, the precision and accuracy was evaluated, obtaining favorable results in the analysis. The calculation of the expanded uncertainty for this method was 0.610 µg/L.